Eristalis horticola - El-Hawagry, Magdi S.; Gilbert, Francis (Zenodo, 2019)
Eristalis horticola (De Geer, 1776) [ERISTALINAE: ERISTALINI] Musca horticola De Geer, 1776: 140. Type locality: Sweden. World distribution : OR: India. PA: Algeria,? Egypt, Europe (Fennoscandia southwards; from Ireland eastwards through much of Europe into Russia and on through Siberia to the Pacific coast (Sakhalin)), Morocco, Tunisia. Egyptian localities : Unknown. Activity period in Egypt : Unknown. Remarks : Eristalis horticola was listed as recorded from Egypt "in the literature" by Steyskal & El-Bialy (1967), repeated by Peck (1988), but no specimens or published records were found in either the Egyptian collections or in the literature listed by Steyskal & El-Bialy. We assume that the name horticola was a misidentification, or perhaps simply a mistake. Published as part of El-Hawagry, Magdi S. & Gilbert, Francis, 2019, Catalogue of the Syrphidae of Egypt (Diptera), pp. 201-248 in Zootaxa 4577 (2) on page 227, DOI:10.11646/zootaxa.4577.2.1, http://zenodo.org/record/2629643